SEMANTICS IN OBEY CLOTHING T-SHIRT DISCOURSE: A STUDY OF SEMANTICS - Jati, Raden Risman (Program Studi Sastra Inggris, Fakultas Sastra, Universitas Komputer Indonesia Bandung, 2019)
In this study, it is analyzed lexical meaning in a text of written language which is applied on Obey’s T-shirt. These meanings furthermore constructed descriptive interpretations. The theory used in this study is theories of lexical semantics in Mansoer Pateda (2010). Reseach method in this study is descriptive analysis which is conducted by using analytic approach and operational approach of lexical meaning. This approach includes meaning component segmentation and lexical meaning analysis. The result of this study which is conducted on eight product samples is that each product has its own characteristic which can be constructed through interpretation based on lexical meaning of each entity in the product. The lexical meaning which is analyzed is capable to construct meaning related to the object outside the language. Both meaning, lexical and cognitive meanings are able to construct an interpretation as a meaning representation of a text as a whole part.